Vision-based speed detection of a mobile robot - Quek, Soon You. (2013)
The aim of this final year project is to implement a vision-based method to detect the speed of a moving robot with the aid of a camera. In this report an optical flow algorithm is proposed for velocity estimation. The algorithm is based on features tracking and computation of optical flow vectors. The algorithm uses function in the OpenCV library and coded in C language. This report consists of literature, methods and results. The development of the project is illustrated inside the project milestones.